An Overview of Corporate Fraud and its Prevention Approach - Md. Abdur Rashid; Abdullah Al-Mamun; Hajar Roudaki; Qaiser Rafique Yasser (Australasian Accounting, Business and Finance Journal, 2022)
Purpose –The purpose of this paper is to provide a review of the literature on corporate fraud as well as financial crime and the prevention approaches used in different contexts. It also aims to find suitable approaches that have effectively been applied to prevent fraud. In addition, this paper attempts to identify the causes and effects of those frauds on the stakeholders of the business. Design/methodology/approach- Based on the review of the literature concerning corporate fraud as well as financial crime from 2003 to 2018. Findings-Focusing on peer-reviewed articles from 2003 to 2018, the study reveals that the internal control system is the most effective approach to prevent and detect corporate fraud which is the component of good governance. Research limitations/implications- Information originates from the selected sources published between 2003 and 2018 in the English language. Hence, a larger sample may yield different results in different countries at a different time. Practical implications- Internal auditors, external auditors, regulatory bodies, the board of directors, and other professionals should recognize these types of frauds and emphasize the importance of these fraud prevention approaches to reduce the likelihood of committing corporate fraud. Originality/value– Provides the comprehensive review and summary of corporate fraud and/or financial crime committed across multiple jurisdictions around the world.
Keywords: Corporate fraud; Financial Crime; Internal Control System; Prevention; Detection; Review; Auditors